THE PRESERVATION OF MARINE FISHERIES RESOURCES WITHIN ASEAN NATIONS’ EEZ - Kurnia, Ida (Indonesia Law Review, 2024)
The preservation of marine fisheries resources within ASEAN nations’ Exclusive Economic Zone (EEZ) is an urgent and pressing challenge requiring collaborative efforts from all ASEAN nations. Challenges such as illegal fishing, climate change, and lack of coordination between ASEAN nations may cause damage to marine biota food chain, especially marine fisheries in Southeast Asia region. To solve this conundrum, collaboration between ASEAN nations pose as the key solution. The research method used in this study is normative juridical approach by analyzing primary legal materials such as International Agreements and other international laws & sources. Further analysis was also conducted from secondary law materials such as international journals and books. It should be noted that the preservation of marine fisheries within ASEAN region has always been a topic that needs to be continuously improved. The urgency to escalate the preservation efforts can be seen in various programs conducted through Ministerial Understanding on Fisheries Cooperation in 1983, as a form of understanding and cooperation between ASEAN nations for the development, management, and conservation of marine fisheries resources within ASEAN EEZ region. Moreover, ASEAN also carried out collaborative efforts for marine fisheries conservation through ASEAN Policy of the General Fisheries Policy Feasibility Study (AGFP). AGFP regulate the ASEAN marine fisheries sector and encompassed 15 focus areas, including marine fisheries resources management, countermeasures against Illegal, Unreported and Unregulated (IUU) Fishing, research on marine fisheries, food security, international trade, animal health, conservation of habitat, and management of marine debris and garbage. The policy was ultimately established by the ASEAN nations member as a Working Unit Forum named The ASEAN Sectoral Working Group on Fisheries (ASWGFi) to realize the vision and mission of AGFP. Efforts to overcome this challenge are laid out by committing to preserve marine fisheries resources in ASEAN nation’s regions, focusing on protecting marine biodiversity – especially marine fisheries resources, encouraging economic and social sustainability, while ensuring food availability and security for the future.